2012
DOI: 10.1371/journal.pntd.0001892
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Wolbachia on Infection with Chikungunya and Yellow Fever Viruses in the Mosquito Vector Aedes aegypti

Abstract: Incidence of disease due to dengue (DENV), chikungunya (CHIKV) and yellow fever (YFV) viruses is increasing in many parts of the world. The viruses are primarily transmitted by Aedes aegypti, a highly domesticated mosquito species that is notoriously difficult to control. When transinfected into Ae. aegypti, the intracellular bacterium Wolbachia has recently been shown to inhibit replication of DENVs, CHIKV, malaria parasites and filarial nematodes, providing a potentially powerful biocontrol strategy for huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
241
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 359 publications
(250 citation statements)
references
References 42 publications
(72 reference statements)
4
241
1
4
Order By: Relevance
“…Several innovative approaches to vector control are in trial, one being population replacement with Wolbachia-infected A. aegypti. These mosquitoes have shorter life spans and high resistance to DENV, CHIKV, and YFV infection, and the intracellular Wolbachia bacteria remains established in the population [52]. However, A. albopictus is unaffected by this technique.…”
Section: Discussionmentioning
confidence: 99%
“…Several innovative approaches to vector control are in trial, one being population replacement with Wolbachia-infected A. aegypti. These mosquitoes have shorter life spans and high resistance to DENV, CHIKV, and YFV infection, and the intracellular Wolbachia bacteria remains established in the population [52]. However, A. albopictus is unaffected by this technique.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, studies have shown that certain microbes associated with insect vectors could be used to mediate the transmission of diseases including those transmitted by mosquitoes (Capone et al., 2013; Cirimotich et al., 2011; Dong, Manfredini, & Dimopoulos, 2009; Mourya, Pidiyar, Patole, Gokhale, & Shouche, 2002; Ramirez et al., 2014; Tchioffo et al., 2013; Xi, Ramirez, & Dimopoulos, 2008), tsetse flies (Pais, Lohs, Wu, Wang, & Aksoy, 2008; Wang, Wu, Yang, & Aksoy, 2009; Weiss, Wang, Maltz, Wu, & Aksoy, 2013), sand flies (Sant'Anna et al., 2014), and ticks (Gall et al., 2016; Narasimhan et al., 2014). The most striking example is the inhibition by bacterium Wolbachia pipientis of virus and parasite infection in mosquito vectors (Bian, Xu, Lu, Xie, & Xi, 2010; Blagrove, Arias‐Goeta, Di Genua, Failloux, & Sinkins, 2013; Frentiu et al., 2014; van den Hurk et al., 2012; Hussain et al., 2012; Moreira et al., 2009). Unfortunately, while studies on the application of microbes such as Wolbachia to control human disease have advanced, we still lack basic insight into the natural microbial communities associated with vectors, from viruses to bacteria to single‐celled eukaryotes.…”
Section: Introductionmentioning
confidence: 99%
“…These findings were unexpected given that Wolbachia has been extensively shown to inhibit flaviviruses of medical importance in Ae. aegypti (Bian et al., 2010; van den Hurk et al., 2012; Moreira et al., 2009; Walker et al., 2011). …”
Section: Discussionmentioning
confidence: 99%
“…aegypti populations. This sharply contrasts previous studies where Wolbachia infection significantly reduced the proportion of individuals infected with other flaviviruses such as DENV (Amuzu & McGraw, 2016; Amuzu, Simmons, & McGraw, 2015; Bian et al., 2013; Frentiu et al., 2014; Moreira et al., 2009; Walker et al., 2011), Zika (Aliota et al., 2016; Dutra et al., 2016), and YFV (van den Hurk et al., 2012). Our findings are, however, supported by studies performed in Cx.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation